Remembering the origins of the Chilean republic: Conservative ideas on national history during the 1930s. - Burgos, Raúl (Journal of Iberian & Latin American Studies, 2024)
This paper examines the relationship between politics and history in Chile in the 1930s. It analyses how Conservative circles, including politicians, members of the Catholic Church, and historians expressed concern about the absence of a real sense of nationhood during this period. It argues that these people articulated a shared discourse that revealed the value of national history as a way to recover traditional political and moral values to bolster a sense of civic nationalism in society. By analysing newspapers, magazines and parliamentary debates, the paper focuses on the role played by these Conservative individuals in the public commemorations of the 1833 constitution and the nineteenth-century statesman Diego Portales (1793–1837).